Banking in the Digital Era: Charting the Path from Transformation to Performance in Indonesian Banks - Saktiawan, Bimo; Dewi, Resfita; Risfandy, Tastaftiyan; Setiyono, Bowo (ETIKONOMI, 2026)
Research Originality: This research develops a new digital transformation adoption measure based on the number of products and services provided by a bank. Research Objectives: This study examines the impact of digital transformation, specifically the adoption of digital services and products, on bank performance in Indonesia. Research Methods: This study used hand-collected data from commercial bank annual reports to determine their digital transformation adoption and the BankFocus BvD database for the banks’ financial data for 2014–2023. This study employed fixed- and random-effects models and the two-step generalized method of moments to address endogeneity. Empirical Results: Digital transformation positively affects banking performance, and the significant effect is heterogeneous in nonstate-owned commercial and small and medium-sized banks. Implications: This study provides policymakers and banking executives with insights into the critical role of digital product and service adoption in overcoming the increasing challenges of modern business. The heterogeneity test results suggest that targeted policies and incentives are needed to create a supportive climate for digital transformation. JEL Classification: G21, G23, G33